2017
DOI: 10.1080/13803395.2017.1372367
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a working memory training in substance use patients: A randomized double-blind placebo-controlled clinical trial

Abstract: Overall, we did not find evidence for the efficacy of WM training on WMC or clinical symptoms as compared to a placebo training in a population of substance use disorder patients. Future research needs to investigate further whether WMC is an important factor that is associated with substance-abuse-related behavior, and whether working memory training could be useful in substance use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…Neurostimulation that targets the dorsolateral prefrontal cortex, a key brain area in working memory (Petrides, 2000), decreases craving across different substances (Jansen et al, 2013). Preliminary findings from targeted cognitive training interventions support the role of WM in reducing or stabilizing drug use in community and clinical samples (Houben, Wiers, & Jansen, 2011;Rass et al, 2015;Verdejo-Garcia, 2016), although recent findings on these interventions are mixed (Khemiri, Brynte, Stunkel, Klingberg, & Jayaram-Lindstrom, 2018;Wanmaker et al, 2018). Yet despite a strong theoretical basis, there are no data evaluating that WM indeed modulates substance craving in association with drug cues or stressful contexts.…”
mentioning
confidence: 99%
“…Neurostimulation that targets the dorsolateral prefrontal cortex, a key brain area in working memory (Petrides, 2000), decreases craving across different substances (Jansen et al, 2013). Preliminary findings from targeted cognitive training interventions support the role of WM in reducing or stabilizing drug use in community and clinical samples (Houben, Wiers, & Jansen, 2011;Rass et al, 2015;Verdejo-Garcia, 2016), although recent findings on these interventions are mixed (Khemiri, Brynte, Stunkel, Klingberg, & Jayaram-Lindstrom, 2018;Wanmaker et al, 2018). Yet despite a strong theoretical basis, there are no data evaluating that WM indeed modulates substance craving in association with drug cues or stressful contexts.…”
mentioning
confidence: 99%
“…Similarly, studies of methadone maintenance (168) and cannabis (169) have found no evidence of far-transfer effects (e.g., delay discounting), although Rass et al (168) showed WMT-related reductions in street drug use among methadone users. Other forms of WMT (e.g., n-back training) have reported similar near-transfer but not substanceuse-related findings with methamphetamine patients (170) and a mixed group of substance use patients (alcohol, cannabis, cocaine) (164). As such, the greatest limitation in the WMT literature is the failure to consistently examine substance use outcomes and therefore there is insufficient evidence at this time to support the utility of WMT as an effective adjunctive treatment for SUD.…”
Section: Working Memory Training (Wmt)mentioning
confidence: 96%
“…WMT aims to extend WM capacity, so individuals can better integrate, manipulate, and prioritize important information, with the aim of supporting more adaptive decisionmaking that leads to reduced substance use (163). Relative to many other approaches, WMT is intensive, typically requiring 19-25 days of training and as such, retention is often poor (164). While WMT has been shown to lead to improvements in neartransfer effects (i.e., improved performance on similar WM tasks), there is limited evidence supporting far-transfer effects of WMT on other measures of EF and importantly, on substancerelated outcomes (165).…”
Section: Working Memory Training (Wmt)mentioning
confidence: 99%
“…In contrast to some studies using formal training of working memory (e.g., [83]) to evaluate their direct impact on unhealthy behaviors (e.g., alcohol abuse), which can be positive in nonclinical samples [84], but not clinical population [85], modified versions of response inhibition tasks have served as training paradigms [79,[86][87][88][89][90].…”
Section: Restoring Inhibitory Controlmentioning
confidence: 99%